INDEPENDENT RESEARCH WORK OF STUDENTS OF A TECHNICAL UNIVERSITY AS AN IMPORTANT CONDITION FOR PREPARING THEM FOR PROFESSIONAL ACTIVITIES - Pogrebnaya, Irina; Mikhailova, Svetlana (Revista Inclusiones, 2020)
The article considers the importance of students' independent research work, its influence on the formation of competencies in accordance with the requirements of federal state educational standards of higher education, which determines their readiness for professional activities of professional activity. Studies of this problem were carried out on the basis of a higher technical educational institution, namely, the Tyumen Industrial University branch in Nizhnevartovsk. The following goals of the organization of students' research work are identified: strengthening and increasing the level of training, formation, multiplication and preservation of the intellectual and scientific and technical potential of young researchers; the generation of high moral qualities of a future specialist and scientist in the spirit of moral and ethical standards inherent in Russian science; application of the scientific and creative potential of students to help Russian science and higher education; consolidation of the most capable and promising students in the scientific plan in the system of science and higher education. Professional mobility (independence) and professional training of future specialists are considered on the example of students' independent work in the process of preparing and conducting practical classes in the discipline "Hydraulics". A certain part of the tasks of independent work is aimed at forming students' readiness for further production and labor activities.